First evidence of free-living Naegleria species in recreational lakes of Alberta, Canada. (17th February 2023) - Dey, Rafik; Dlusskaya, Elena; Oloroso, Mariem; Ashbolt, Nicholas J.
Abstract: Rising temperatures are increasing environmental habitats for thermotolerant pathogens, such as the so-called 'brain-eating amoeba', Naegleria fowleri . To the best of our knowledge, however, Naegleria species have not been reported in environmental water sources in Canada. We surveyed popular recreational lakes in Alberta, Canada during the summer bathing period to determine the presence or absence of Naegleria species. While N. fowleri was not isolated in this study, we identified other thermotolerant species, including Naegleria pagei, Naegleria gruberi, Naegleria jejuensis and Naegleria fultoni using culture-based methods, hence indicating the potential conditions to support N. fowleri . Ongoing monitoring and examination of water for pathogenic amoebae is recommended in order to assist in the public health management of water sources. HIGHLIGHTS: Survey of Naegleria species in recreational lakes in Alberta, Canada. First evidence of thermotolerant Naegleria species detection in Canada. Climate change and northern expansion of Naegleria species.